ADDING DIFFERENT LEVELS OF TURMERIC POWDER AND CURCUMIN IN THE DIET ON BROILER PERFORMANCE, CARCASS TRAITS, IMMUNITY AND GUT MORPHOLOGY OF BROILER CHICKEN UNDER NORMAL AND HEAT STRESS CONDITION - Mustafa, M. M.; Karadas, F.; Tayeb, I. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted to estimate the effect of adding different levels of turmeric powder and curcumin on broiler performance, carcass traits, and immunity response and jejunum histology. A total of 750 Ross day old chicks obtained from a local hatchery and distributed into two rearing conditions (normal and heat stress condition) with five treatments 3 replicate for each one had (25 chicks). Dietary supplements of turmeric powder and curcumin significantly (P ≤ 0.05) improved performance under normal and heat stress conditions. Moreover, treatments significantly (P ≤ 0.05) increased the total titter antibody against Newcastle and infectious bursal disease compared to control. Concerning histology of jejunum treatments significantly (P≤0.01) improved jejunum histology. Regarding the effect of rearing condition heat stress conditions significantly (P ≤ 0.01) decreased performance compared to normal rearing condition. Small intestine percent from live body weight significantly (P ≤ 0.01) decreased compared to normal rearing conditions. Moreover, heat stress significantly (P≤0.01) affected the total antibody titer against Newcastle disease and infectious bursal disease. Jejunum histology significantly (P ≤ 0.01) affected by rearing conditions.